PENEGAKAN HUKUM TERHADAP PENCEMARAN LINGKUNGAN HIDUP DI INDONESIA - Sri Hartati (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2018)
Law enforcement against pollution and environmental destruction include : (a). Lawenforcement efforts, both preventively, by providing counseling to industry actorsand to surrounding communities to participate in maintaining and preserving theenvironment. (b). The EIA also becomes one of the main requirements in obtaining anabsolute environmental permit prior to obtaining a business license. (c). Any processof formulation and application of pollution prevention and/or environmentaldamage and mitigation and law enforcement instruments requires the integration ofaspects of transport, participators, accountability and fairness. Preventive effortsundertaken by the apparatus include, counseling and monitoring of the communityby building stake holders commitment in their perceptions and cooperation tomaintain, preserve and manage the environment as well as preventive efforts. Whilerepressive efforts by the apparatus are dealing with the investigation to the forefrontof the threat of criminal, civil, and administrative sanctions. But of the three effortsthat are most often done is an effort with the instrument in a preventive mannerwithout waiting for the occurrence of environmental disputes.